Organochlorine Pesticides and Polychlorinated Biphenyls in Blue Crabs Callinectes sapidus (Rathbun, 1896) from Akyatan Lagoon in the Eastern Mediterranean Region of Turkey. - KILERCIOGLU, BIGE GULMEN; CENGIZLER, IBRAHIM; DAGLIOGLU, NEBILE; KILERCIOGLU, SERDAR (Mediterranean Marine Science, 2018)
The aim of this study is to determine the levels of organochlorine-based pesticides and polychlorinated biphenyls in the edible muscle tissue of blue crabs Callinectes sapidus (Rathbun, 1896) that are harvested from Akyatan Lagoon in the Eastern Mediterranean Region of Turkey. The crabs were harvested in October 2010, January 2011 and March 2011. A total of fifty crabs were studied. A quantitative determination of residue levels was carried out through a Gas Chromatography-Electron Capture Detector (GC-ECD), and compared with acceptable contaminant levels. PCBs were the greatest source of contamination.. The predominant compounds were α-HCH, o,p’-DDE, PCB 28 (2,2',4,4'-PCB) and PCB 52 (2,2’,5,5’-PCB), with mean concentrations of 22.39, 59.45, 347.31 and 362.86 ng/gwet weights, respectively. The present work is highly significant and points out a chronic exposure to pollutants in Akyatan Lagoon. This ecosystem is protected under the Ramsar Convention (Convention on Wetlands of International Importance, especially as Waterfowl Habitat).